Recruitment, selection, and training of new workers based on resilience skills: a study with grid electricions and distribution control center operators - Alves, Alexandre Eberle (2018)
O The convergence of technical skills with resilience contributes to foster an environment that works safely and efficiently. Through Resilience Engineering, the objective of this search is to obtain a system in which the functioning of the process is maintained during misfortunes, or unexpected events. The main goal of this article is to identify resilience skills while performing emergency maintenance activities and diagnosing problems in the electrical network during events involving equipment failures at an energy distributor. This paper approaches the activities of the operators of the Distribution Operations Center (COD) of the company in the study, on order to: (1) investigate the procedures used in the recruitment and selection process of the company to verify whether resilience skills are included, and (2) propose improvements in the training process to facilitate and minimize the identified need for resilience skills.